The earliest records of Jesus - Beare, Francis Wright (Oxford, UK Basil Blackwell, 1962)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Synoptic gospels -- criticsm, interpretation, etc; Jesus Christ -- history of doctrines